New design of a variable impedance based on polarized diodes at microwave frequency - Venere, Alejandro Javier (2017)
In this letter, we present a new variable impedance termination consisting of two polarized diodes. To generate a complex-valued impedance, two controlled current sources polarize the diodes, which are interconnected with a Wilkinson power divider through transmission lines of different electric lengths. Because of the reduced number of diodes, this structure presents low power consumption and simple control. We validated the proposed design by implementing a prototype at the operating frequency of 1575.42 MHz. Mapping the measured results in the Smith chart, the impedance can produce reflection coefficients with full-phase coverage within the circle of magnitude 0.35 over a frequency range of 1.5-1.6 GHz.